DETERMINAN NILAI PERUSAHAAN LQ 45 DI BURSA EFEK INDONESIA - Febri Yunita (2020)
This research was conducted to test profitability, capital structure, and investment decisions on firm value. This research was conducted at LQ 45 companies listed on the Indonesia Stock Exchange. The sampling technique uses the saturation sampling method. 45 samples of companies listed on the LQ 45 index and listed on the Indonesia Stock Exchange in 2015-2019. Data analysis was performed using Microsoft Excel 2013 and hypothesis testing in this study used panel data regression analysis with the E-views program 10 and a probability level of 5% (0.05). The results of this test are obtained (1) Profitability has a positive effect on firm value, (2) Capital structure has no effect on firm value, (3) Investment decisions have no effect on firm value.